The given functions are
![f(x) = (3)/(x-5) , g(x) = (3+5x)/(x)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/awlwh40mmnk6f665enfax2t1sz6gazwaxj.png)
First we find fog(x)= f(g(x))
So we need to substitute the value of g(x) for x in f(x), that is
![f(g(x)) = (3)/((3+5x)/(x)-5) = (3x)/(3+5x-5x)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8k670bawuvokqz5kvctvjwwc94i5e0y7za.png)
![= (3x)/(3) = x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/59wmzcw5s1rcxsjetmc3hxy8d53q6m44xi.png)
Now we need to check the value of gof(x)
gof(x) = g(f(x))
So we need to substitute the value of f(x) in g(x), that is
![g(f(x))=(3+5*(3)/(x-5))/((3)/(x-5))= (3x-15+15)/(3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2ovmfa2vje89gjx4s43an1dnn43fypjxf5.png)
![=(3x)/(3) = x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/epsyqnpc5ovlnpb4gc8x6g8r221ifxp18z.png)
And since
![fog(x) =gof(x) =x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/yx9tc9no352h0mqd7m9ba34pzooieua1k8.png)
So the functions are inverse of each other .
Correct option is C .